Effect of Inhalational Anesthetics and Positive-pressure Ventilation on Ultrasound Assessment of the Great Vessels: A Prospective Study at a Children's Hospital. (April 2016) - Lin, Elaina E.; Chen, Aaron E.; Panebianco, Nova; Conlon, Thomas; Ju, Na Rae; Carlson, Dustin; Kopenitz, Jason; Nishisaki, Akira
Abstract : Background: Bedside ultrasound has emerged as a rapid, noninvasive tool for assessment and monitoring of fluid status in children. The inferior vena cava (IVC) varies in size with changes in blood volume and intrathoracic pressure, but the magnitude of change to the IVC with inhalational anesthetic and positive-pressure ventilation (PPV) is unknown. Methods: Prospective observational study of 24 healthy children aged 1 to 12 yr scheduled for elective surgery. Ultrasound images of the IVC and aorta were recorded at five time points: awake; spontaneous ventilation with sevoflurane by mask; intubated with peak inspiratory pressure/positive end-expiratory pressure of 15/0, 20/5, and 25/10 cm H2 O. A blinded investigator measured IVC/aorta ratios (IVC/Ao) and changes in IVC diameter due to respiratory variation (IVC-RV) from the recorded videos. Results: Inhalational anesthetic decreased IVC/Ao (1.1 ± 0.3 vs. 0.6 ± 0.2; P < 0.001) but did not change IVC-RV (median, 43%; interquartile range [IQR], 36 to 58% vs. 46%; IQR, 36 to 66%; P > 0.99). The initiation of PPV increased IVC/Ao (0.64 ± 0.21 vs. 1.16 ± 0.27; P < 0.001) and decreased IVC-RV (median, 46%; IQR, 36 to 66% vs. 9%; IQR, 4 to 14%; P < 0.001). There was no change in either IVC/Ao or IVC-RV with subsequent incremental increases in peak inspiratory pressure/positive end-expiratory pressure ( P > 0.99 for both). Conclusions: Addition of inhalational anesthetic affects IVC/Ao but not IVC-RV, and significant changes in IVC/Ao and IVC-RV occur with initiation of PPV in healthy children. Clinicians should be aware of these expected vascular changes when managing patients. Establishing these IVC parameters will enable future studies to better evaluate these measurements as tools for diagnosing hypovolemia or predicting fluid responsiveness. Abstract : Inhalational anesthesia decreased the inferior vena cava (IVC)/aorta ratio but did not change the IVC diameter in response to respiratory variation in healthy children receiving general anesthesia. The initiation of positive-pressure ventilation significantly increased the IVC/aorta ratio and decreased the IVC diameter in response to respiratory variation. There was no change in the IVC/aorta ratio or the IVC diameter in response to respiratory variation with subsequent incremental increases in peak inspiratory pressure or positive end-expiratory pressure.